2018
DOI: 10.1080/01616412.2018.1453190
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation in the modulation of neuropathic pain: a systematic review

Abstract: Objective To investigate the neuromodulating effect of Transcranial Direct Current Stimulation (tDCS) on Neuropathic Pain (NP). Method A systematic review of articles published in the past five years in MEDLINE, LILACS, Cochrane, Scopus, ScienceDirect, and PEDro. The search was carried out from February to May 2017 using the keywords: neuropathic pain, neuralgia, nerve pain, central pain, peripheral nerve pain, tDCS. The selected studies were full articles written in Portuguese, English, or Spanish with at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Past studies have suggested that the hypoalgesic effect of tDCS and TENS could be cumulative, with individuals reporting greater pain relief with increasing number of sessions. 21,50 Although we cannot rule out a cumulative effect of tDCS, the results obtained following the second tDCS+TENS intervention (Treatment C, given 6 months later) somewhat argues in favor of a more potent effect of the combination of treatments, although both mechanisms could be simultaneously involved. The number of tDCS +TENS sessions required to optimally relieve pain is still unknown, but our observations could suggest that increasing the number of tDCS/TENS treatments could possibly lead to greater effects.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Past studies have suggested that the hypoalgesic effect of tDCS and TENS could be cumulative, with individuals reporting greater pain relief with increasing number of sessions. 21,50 Although we cannot rule out a cumulative effect of tDCS, the results obtained following the second tDCS+TENS intervention (Treatment C, given 6 months later) somewhat argues in favor of a more potent effect of the combination of treatments, although both mechanisms could be simultaneously involved. The number of tDCS +TENS sessions required to optimally relieve pain is still unknown, but our observations could suggest that increasing the number of tDCS/TENS treatments could possibly lead to greater effects.…”
Section: Discussionmentioning
confidence: 88%
“…The number of tDCS +TENS sessions required to optimally relieve pain is still unknown, but our observations could suggest that increasing the number of tDCS/TENS treatments could possibly lead to greater effects. 21 The higher pain level noted during the pretreatment period of Treatment C could also have influenced our results. Still, the difference between the pretreatment pain intensity (Pre-Tx) of logbook 1 and logbook 2 are not clinically significant.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hence, tDCS is a promising technique because it modulates the thalamocortical synapses in a top-down manner within pain pathways7 and it might change in thalamic inhibitory pathways, cingulate cortex, and periaqueductal gray matter induced by tDCS 8106 and chronic pain (eg, trigeminal neuralgia, phantom pain, and fibromyalgia) 11…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation, which spans a broad range of implanted and non-invasive modalities, may have a potential role in the treatment of COVID-19 related symptoms. This potential is theorized based on the known mechanisms of biological action, demonstrated benefits in non-COVID-19 patients for various known sequelae of COVID-19 illness and recovery (Lefaucheur et al, 2017;David et al, 2018;Ghosh, 2019;Razza et al, 2020), with initial reports of its application in COVID-19 patients (Azabou et al, 2020;Bonaz et al, 2020;Kaniusas et al, 2020;Shinjo et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%